2022
DOI: 10.1111/eva.13360
|View full text |Cite
|
Sign up to set email alerts
|

Effective specialist or jack of all trades? Experimental evolution of a crop pest in fluctuating and stable environments

Abstract: Understanding pest evolution in agricultural systems is crucial for developing effective and innovative pest control strategies. Types of cultivation, such as crop monocultures versus polycultures or crop rotation, may act as a selective pressure on pests' capability to exploit the host's resources. In this study, we examined the herbivorous mite Aceria tosichella (commonly known as wheat curl mite), a widespread wheat pest, to understand how fluctuating versus stable environments influence its niche breadth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 177 publications
0
6
0
Order By: Relevance
“…The presence of genetic variation can also be inferred from experimental evolution responses. Numerous studies using this methodology have documented the rapid evolution of host range (Sousa et al ., 2019; Mortier & Bonte, 2020; Laska et al ., 2021; Olazcuaga et al ., 2021; Skoracka et al ., 2022) and dispersal (Belliure, Montserrat & Magalhães, 2010; Bitume et al ., 2011; Fronhofer et al ., 2014; De Roissart et al ., 2016; Lustenhouwer et al ., 2023) in herbivores. Such responses imply that sufficient genetic variation for these traits is present in the original population.…”
Section: Empirical Studies On the Interplay Between Specialisation An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of genetic variation can also be inferred from experimental evolution responses. Numerous studies using this methodology have documented the rapid evolution of host range (Sousa et al ., 2019; Mortier & Bonte, 2020; Laska et al ., 2021; Olazcuaga et al ., 2021; Skoracka et al ., 2022) and dispersal (Belliure, Montserrat & Magalhães, 2010; Bitume et al ., 2011; Fronhofer et al ., 2014; De Roissart et al ., 2016; Lustenhouwer et al ., 2023) in herbivores. Such responses imply that sufficient genetic variation for these traits is present in the original population.…”
Section: Empirical Studies On the Interplay Between Specialisation An...mentioning
confidence: 99%
“…Therefore, the role of temporal host variability in selecting for specialists or generalists in plant–herbivore systems in the field remains in need of study, in part because it is difficult to establish the true host range of herbivores in temporally variable landscapes (Laska et al ., 2021). Studies on experimental evolution have shown that temporal variation affects different life‐history traits in herbivores (Magalhães et al ., 2014; De Roissart et al ., 2016) including dispersal (Fronhofer et al ., 2014) and host range (Skoracka et al ., 2022). However, studies measuring both traits are lacking.…”
Section: Theoretical Explanations For the Absence Of A Correlationmentioning
confidence: 99%
“…They must cope with miscellaneous abiotic stresses usually enhanced by heavy industry ( Labudda et al., 2022 ). Moreover, changes in climate conditions and agricultural systems are favourable to pests and pathogens gradation on plants ( Nykiel et al., 2022 ; Skoracka et al., 2022 ). However, plants are not defenceless; they are equipped with a battery of multiple mechanisms (from molecular through biochemical-physiological to structural) that are activated by them to ensure further growth and development and the production of diasporas ( Muszyńska and Labudda, 2019 ; Formela-Luboińska et al., 2020 ; Tokarz et al., 2020 ; Tokarz et al., 2021 ; Fidler et al., 2022 ; Miernicka et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such responses are energetically costly and therefore need to be compensated by either increased resource intake 5,19 , or by diverting resources away from reproduction in favour of cellular maintenance 20,31 . Such alternative strategies in pest species' life-history are predicted to impact both their invasion potential and the footprint left on their hosts 1,14,17,[32][33][34] , and thus, can have important consequences for pest management 1,3,35 .…”
mentioning
confidence: 99%